Development of Web-Based Rtikabdimas Application With a Rapid Unified Process Approach - Rinda Cahyana; Ridwan Setiawan; Ihsan Nugraha (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2023)
RTIKAbdimas is one of the annual routine ICT Volunteer programs in Indonesia. ICT volunteers use the website for information delivery, communication, and registration. Previous research has uncovered implementing and developing web platforms that support similar or benefit such programs, including information services, communications, registration, and online monitoring. Existing research still needs to provide a complete solution to the problem of printed files and manual methods in the RTIKAbdimas business process. This study aims to develop a web-based RTIKAbdimas application using the Rapid Unified Process approach by adopting and complementing existing research results for different problems. This research has succeeded in meeting the system specifications of the RTIKAbdimas business process and includes several online services on web applications developed by previous research. All actors have a dashboard to enter data and access information on data processing results. The most crucial benefit of this research is the control and time efficiency of the activities of actors other than program managers.